Head and heart : valour and self-sacrifice in the art of India - Mary Storm (Routledge, 2013)
An extensive study of self-sacrificial images in Indian art, this book examines concepts such as head-offering, human sacrifice, blood, suicide, valour, self-immolation, and self-giving in the context of religion and politics to explore why these images were produced and how they became paradigms of heroism.